The stability of grounding lines on retrograde slopes - Gudmundsson, G. H.; Krug, J.; Durand, Geoffroy; Favier, L.; Gagliardini, O. (The Cryosphere, 2012)
International audience The stability of marine ice sheets grounded on beds that slope upwards in the overall direction of flow is investigated numerically in two horizontal dimensions. We give examples of stable grounding lines on such retrograde slopes illustrating that marine ice sheets are not unconditionally unstable in two horizontal dimensions. Retrograde bed slopes at the grounding lines of marine ice sheets, such as the West Antarctic Ice Sheet (WAIS), do not per se imply an instability, nor do they imply that these regions are close to a threshold of instability. We therefore question those estimates of the potential near-future contribution of WAIS to global sea level change based solely on the notion that WAIS, resting on a retrograde slope, must be inherently unstable.